Activation of Carbohydrate Response Element-Binding Protein by Ethanol. (February 2013) - Liangpunsakul, Suthat; Ross, Ruth A.; Crabb, David W.
Objective: Carbohydrate response element-binding protein (ChREBP) is a transcription factor involved in hepatic lipogenesis. Its function is in part under the control of AMP-activated protein kinase (AMPK) and protein phosphatase 2A (PP2A). Given known effects of ethanol on AMPK and PP2A, it is plausible that ethanol might enhance fatty acid synthesis by increasing the activity of ChREBP. We hypothesized that another potential pathway of ethanol-induced hepatic steatosis is mediated by activation of ChREBP. Methods: The effects of ethanol on ChREBP were assessed in hepatoma cells and in C57BL/6J mice fed with the Lieber-DeCarli diet. Results: When the cells were exposed to ethanol (50 mM) for 24 hours, the activity of a liver pyruvate kinase (LPK) promoter-luciferase reporter was increased by ∼4-fold. Ethanol feeding of mice resulted in the translocation of ChREBP from cytosol to the nucleus. Protein phosphatase 2A activity was increased in the liver of ethanol-fed mice by 22%. We found no difference in the levels of hepatic Xu-5-P between ethanol-fed mice and controls. Transfection of a constitutively active AMPK expression plasmid suppressed the basal activity of the LPK luciferase reporter and abolished the effect of ethanol on the reporter activity. However, transfection of rat hepatoma cells with a dominant-negative AMPK expression plasmid induced basal LPK luciferase activity by only ∼20%. The effect of ethanol on ChREBP was attenuated in the presence of okadaic acid, an inhibitor of PP2A. Conclusions: The effects of ethanol on AMPK and PP2A may result in activation of ChREBP, providing another potential mechanism for ethanol-induced hepatic steatosis. However, additional okadaic acid-insensitive effects appear to be important as well.